The Influence of Arabic Language Mastery on The Ability to Memorize The Qur'an in At-Tajdid Islamic Boarding School - Helmi Gunawan; Tita Amelia (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
Regarding the field of Islamic education, the name Al-Qur'an cannot be avoided, because Al-Qur'an is a guide or guide to human life. According to the definition, Al-Qur'an is kalamullah, which is a miracle revealed to the Prophet Muhammad SAW, and reading it is an act of worship. The objective of the research is mastery of Arabic affects the ability to memorize Al-Qur'an in At-Tajdid Islamic Boarding School students. Al-Qur'an occupies a position as the first and main source of all Islamic teachings and also functions as a guide or guide for mankind in achieving happiness in this world and the afterlife. This research uses a qualitative research method which uses methods, steps, and procedures that involve data and information obtained through respondents as subjects who can express their answers and feelings to get a holistic general picture of a detailed matter. The research subject is the information about how mastery of Arabic will affect the ability to memorize Al-Qur'an in At-Tajdid Islamic Boarding School students. The researcher uses questionnaires and interviews about how mastery of Arabic affect the ability to memorize Al-Qur'an in At-Tajdid Islamic Boarding School students. The result of the research is that mastery of Arabic has a huge influence on the ability to memorize the Al-Qur'an for female students at the At-Tajdid Cepu Islamic Boarding School. Where mastery of Arabic can be learned by providing gradual training to students. It shows the average student’s answer 74.75